PENGARUH KONSENTRASI GULA LARUTAN MOLASES TERHADAP KADAR ETANOL PADA PROSES FERMENTASI - Agus Rochani; Susy Yuniningsih; Zuhdi Ma'sum (Universitas Tribhuwana Tunggadewi Malang, 2016)
The imbalance between supply and fuel needs led to the impact of the energy crisis. Bioethanol is an alternative fuel that has the potential to replace fossil fuels. Bioethanol is the result of fermentation of biomass ethanol with the aid of microorganisms. This study aims to determine the ethanol content is influenced by the concentration of the solution of sugar molasses, as well as determine how much sugar concentration in the most optimal fermentation of molasses (molasses). The fermentation process varied with the concentration of 12%, 14%, 16%, 18%, 19% and 20%. To determine levels of ethanol produced, then the measurement or test the ethanol content in each variable concentrations of sugar substrate by means of pycnometer. The results showed that the concentration of the solution of sugar molasses effect on levels of ethanol produced. The highest ethanol content obtained at a concentration of 18% sugar, amounting to 13.85%. Lowest ethanol content obtained at a concentration of 12% sugar, namely 4.56%, while the sugar concentration of 14% - 18% ethanol continues to increase in a row to 6.4%, 12%, and 13.85%. Cereviseae Saccharomyces fermentation activity declined at a concentration of 19% sugar and 20%, ethanol is converted decreased to 11.82% and 8.07%.